Polyethylene Glycol Loxenatide (PEX-168) Reduces Body Weight and Blood Glucose in Simple Obese Mice - Yuting Wu; Zeyuan Guo; Junlu Wang; Yong Wang; Daorong Wang; Ying Li; Lihua Zhu; Xiaofang Sun (International Journal of Endocrinology)
Background. At present, there is a lack of drug treatment for obese patients, so it is needed to find a drug that is effective and has few side effects to treat obesity. PEX-168 is a novel long-acting glucagon-like peptide-1 receptor agonist for T2DM. It improves blood glucose with fewer side effects. The aim of the present study was to investigate the effect of PEX-168 on blood glucose and body weight of mice with simple obesity. Methods. Thirty healthy and 6-week-old C57BL/6 male mice were randomly divided into a normal control group (NC, n = 6) and obesity model group (n = 24). The obesity model mice were randomly divided into a high-fat diet group (HF) and intervention groups with different doses of PEX-168 (0.03 mg/kg, 0.1 mg/kg, and 0.3 mg/kg). Each group includes 6 mice. Body weight, food intake, and fasting blood glucose (FBG) were evaluated after intraperitoneal injection, and the intervention was performed weekly for 12 weeks. Fasting insulin (FINS) levels were measured at the 12th week. Results. Compared with HF, the food intake of mice in the intervention groups decreased transiently, but there was no difference between different doses (P>0.05). The body weight of mice in the middle and high dose of PEX-168 intervention groups decreased significantly, and the differences were statistically significant (P<0.05). The administration of PEX-168 can effectively improve the blood glucose of obese mice, the difference was statistically significant (P<0.05), but there was no difference between different doses (P>0.05). At the 10th week, the incidence of transient hypoglycemia was 67% and 50% in the middle- and high-dose groups, respectively. The levels of serum FINS in the intervention groups were significantly lower than those in the HF group, and the differences were statistically significant (P<0.05), but there was no difference between different doses (P>0.05). Conclusions. PEX-168 showed significant improvement in the FBG and FINS levels of simple obese mice. Middle and high doses of PEX-168 could reduce the weight of simple obese mice, but there was a certain risk of hypoglycemia.